2021
DOI: 10.1080/13510002.2021.1948774
|View full text |Cite
|
Sign up to set email alerts
|

Sestrin2 in hypoxia and hypoxia-related diseases

Abstract: Objectives: Sestrin2 is a stress-inducible protein and play an important role in adapting stress states of cells. This article reviewed the role of Sestrin2 in hypoxia and hypoxia-related diseases to provide new perspectives for future research and new therapeutic targets for hypoxia-related diseases. Methods: A review was conducted through an electronic search of PubMed and Medline databases. Keywords included Sestrin2, ROS, hypoxia, and hypoxia-related disease. Articles from 2008 to 2021 were mostly included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Sestrin2 has a dual function, which can directly reduce oxidative stress by restoring peroxiredoxin peroxide and indirectly reduce oxidative stress by regulating mTOR to enhance autophagy activity (Chen et al 2021a ). Sestrin2 plays a key role in various cell signal transduction processes, and its dysregulation has been linked to various diseases (Che et al 2021 ). For example, calycosin has an inhibitory effect on papillary thyroid cancer by promoting apoptosis and autophagy through the Sestrin2/AMPK/mTOR pathway (Qu et al 2022 ), and studies have shown that Sestrin2 is involved in the regulation of ferroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Sestrin2 has a dual function, which can directly reduce oxidative stress by restoring peroxiredoxin peroxide and indirectly reduce oxidative stress by regulating mTOR to enhance autophagy activity (Chen et al 2021a ). Sestrin2 plays a key role in various cell signal transduction processes, and its dysregulation has been linked to various diseases (Che et al 2021 ). For example, calycosin has an inhibitory effect on papillary thyroid cancer by promoting apoptosis and autophagy through the Sestrin2/AMPK/mTOR pathway (Qu et al 2022 ), and studies have shown that Sestrin2 is involved in the regulation of ferroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…As a sensitive stress receptor, Sestrin2 is activated in stress conditions. A variety of adverse stresses could promote Sestrin2 expression, such as oxidative stress, ER stress, hypoxia, energetic stress, and age-and obesity-associated metabolic pathological conditions (7)(8)(9)(10). Up-regulated Sestrin2 exerts pleiotropic biological effects in diverse physiological and pathological states, through attenuating oxidative stress, and modulating a series of cellular events such as autophagy, ER stress, mitochondrial biogenesis, protein synthesis, cell energy homeostasis and apoptosis, while many of these responsive pathways are interconnected (5,(11)(12)(13)(14).…”
Section: Sestrinpathways and Modulating Mechanismsmentioning
confidence: 99%
“…4 Sestrin2 plays a key role in various cell signal transduction processes, and its dysregulation is associated with various diseases. 5 Pasha M et al have found that the up-regulation of Sestrin2 under oxidative stress enhances the autophagy-directed degradation of Keap1, which targets and degrades nuclear factor erythroid-2-related factor 2 (Nrf2). 6 Nrf2 is a pleiotropic protein that regulates the cellular defense against toxic and oxidative insults.…”
Section: Introductionmentioning
confidence: 99%